Performance of the hospital pharmacist in the Intensive Care Unit (ICU) (Research, Society and Development, 2021)
Known as one of the oldest professions, pharmacy has as its main objective the patient's quality of life. The pharmacist is the professional prepared to guide the correct use of medicines and can act in several areas, such as: the hospital pharmacy that provides a fundamental activity service regarding the correct and rational use of medicines. The objective of this research is to expose the importance of the hospital pharmacist along with the multidisciplinary team of the Intensive Care Unit (ICU). The methodology used was the bibliographic survey of articles in online platforms "Scielo, google academic and Lilacs" and official sites as SBRAFH, AMIB and CFF.  The research shows the advantage of this professional in the multidisciplinary team, solving or preventing negative clinical outcomes caused by the use of medications. Therefore, the performance of the hospital pharmacist is advantageous for both the team and the patient, reducing prescription errors, failures in drug administration, which can bring harm to health, has a good interaction with the other professionals who provide service, thus improving the chances of survival of the critically ill patient, a more effective and less long-lasting treatment.